A Quantitative Evaluation of Electric Sit-Stand Desk Usage: 3-Month In-Situ Workplace Study. Issue 2 (3rd April 2018) - Sharma, Pankaj Parag; Benden, Mark; Mehta, Ranjana K.; Pickens, Adam; Han, Gang
OCCUPATIONAL APPLICATIONS: Sit-stand desk interventions are deployed to reduce sedentary time and improve ergonomic adjustability in modern workplaces, with ultimate goals of improving health and productivity. Sit-stand desks, however, require workers to take an active role in changing the desk position, and usage compliance of the sit-stand function has been a challenge. This study used computer software to objectively record continuous data on electric sit-stand desk usage during computer use, to understand current desk usage behaviors in a large office environment involving ∼300 workers for 3 months. We found that workers completed roughly one desk position change per work day, and one-fourth of the workers always had the desk in a seated position (during computer use). The methods used here demonstrate a novel approach to record sit-stand desk usage continuously during active computer use.